Molecular identification and antifungal susceptibility profiles of etiologic agents of oral candidiasis among HIV-positive patients: A multicenter study - Hamid Morovati; Malihe Jokari; Saba Eslami; Kamiar Zomorodian; Katayoun Taeri; Nesa Khalaf; Hossein Khodadadi (Mazandaran University of Medical Sciences, 2023)
Background and Purpose: Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) is a serious risk factor for oral candidiasis (OC). In this regard, the present study aimed to investigate the frequency of Candida species collected from the oropharyngeal cavity of HIV-positive patients and the sensitivity of these isolates to antifungal drugs.Materials and Methods: Oral samples were collected from 169 HIV-positive patients. In addition to culture-based methods, a molecular assay via the polymerase chain reaction restriction fragment length polymorphism method was applied to identify isolates using the MspI restriction enzyme. The disk diffusion method determined the susceptibility of isolated yeasts to common antifungal drugs according to the CLSI M44-A2 protocol.Results: In total, 81 participants (47.92%) were positive for OC, and Candida albicans was the most prevalent yeast (53.98%). The median age of patients was 36 years old (IQR=10.5; 17-59), and it was found that women are 27% more susceptible to HIVassociated OC (OR=1.268; 95% CI: 0.685-2.348). Patients who received antifungal therapy had a 97.3% reduced chance for OC (OR: 0.027; 95% CI: 0.008-0.091; P-value: 0.000). Antifungal therapy reduced the risk of OC by 97.3% (OR=0.027; 95% CI=0.008- 0.091; P=0.000), and antiretroviral therapy decreased the chance of OC 4.42 times (OR=4.423; 95% CI=1.697-11.528; P=0.002). The resistance rates for antifungals, namely fluconazole, ketoconazole, itraconazole, amphotericin B, and nystatin were 15.93%,8.85%, 7.96%, 5.31%, and 4.42%, respectively.Conclusion: Although several decades have passed since the emergence of HIV/AIDS,little information is available about fungal colonization and infections in this population. Further investigations are suggested using novel and reference molecular identification methods, such as matrix-assisted laser desorption ionization time-of-flight mass spectrometry and sequencing, respectively. In addition, more reliable methods for antifungal susceptibility testing are recommended.